RISK ASSESSMENT OF CLORINE GAS (CL2) AND METHANE (CH4) OF GARBAGE IN DKI JAKARTA USING THE EQC MODELLING AND AIR-WATER MODELING - Zam Zam, Zulkifli (Green Earth, 2012)
The garbage case nowadays become a main issue every where because it needs serious treatment. The dangers related to the characteristics of materials commonly used in households is the materials that contain chemical compounds amunium (CH4) and chlorine (Cl2). This research used the fugacity model approach from ChemCan model including EQC software model and Air-Water Model, in which the structure of the model meets the rules of contamination verification in chemical pathway. To complete the analysis of the impact, it used Material Safety Data Sheet (MSDS) and CAS Number. The results showed that the distribution of Cl 2 in TPA using Model AirWater Â obtined the chlorine concentrations (Cl2) in the air is 1.5 x 10-5 g per m3, 4.32% aerosol, and water 0.015 g/m3. Cl2 compounds found in leachit is 0.015 g/m3 with the ability of evaporation (volatilization) into the air is 3.6 X 107 ug / day. For the distribution of CH4 using the EQC Model In TPA, the concentration of CH4 in the air (level 3) is smaller than in TPS at level 1 and level 2 is greater than, this is due to the TPA has a lot of CH4 reaction and advection into the environment. Reaction and advection in the air increase the amount of CH4 gas in the atmosphere that can cause global warming.Â Key word: Risk Assesment, Gas Clorine, Gas Metan, Sampah, EQC Model, Air Water Model.